THE EFFECTIVENESS OF THE PROJECT BASED LEARNING MODEL FOR SELF REGULATED LEARNING: A CASE STUDY OF POST-PANDEMIC ELEMENTARY SCHOOL SCIENCE LEARNING - Anita Ekantini (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
After the Covid-19 Pandemic, face-to-face (FTF) learning was adopted in elementary schools in the province of the special region of Yogyakarta. However, the introduction of online learning came with its own set of issues, particularly those relating to student learning self-regulation. After adjusting to online learning for at least two years, students must readjust. The purpose of this study is to assess the efficiency of the Project Based Learning (PjBL) learning paradigm for Self Regulated Learning (SRL) students in scientific learning following the Covid-19 pandemic. This study uses the experimental method of Pretest-Posttest Control Group Design. The research was conducted at a islamic elementary school in Yogyakarta in the 2021/2022 school year. The population of this study were students of class IV consisting of 4 classes namely A, B, C, and D. The samples of this study were students of class IV A, totaling 23 students as the control class and IV C, totaling 21 students as the experimental class. Selection of control and experimental classes using cluster random sampling technique. The research findings show that the PjBL model is effective in improving students' SRL in science subjects post-pandemic.